Dynamic perfect hashing: upper and lower bounds - Dietzfelbinger, M.; Karlin, A.; Mehlhorn, K.; Meyer auf der Heide, Friedhelm; Rohnert, H.; Tarjan, R.E. ([Proceedings 1988] 29th Annual Symposium on Foundations of Computer Science)

On computations with integer division - Just, Bettina; Mathematik, Fb; Meyer auf der Heide, Friedhelm; Informatik, Fb; Wigderson, Avi (STACS 88)

Upper and lower bounds for the dictionary problem - Dietzfelbinger, M.; Mehlhorn, K.; Meyer auf der Heide, Friedhelm; Rohnert, H. (SWAT 88)

Enhancement Techniques in Digital Image Processing - Domik, Gitta (Proceedings of the Computer Science Symposium)

A multi-spectral analysis system using large databases. - Brugel, Edward W; Domik, Gitta; Voels, Stephen A (European Southern Observatory Conference and Workshop Proceedings)

Dependence of image grey values on topography in SIR-B images - Domik, Gitta; Leberl, Franz; Cimino, J (International Journal of Remote Sensing)

SIR-B stereo-radargrammetry of Australia - Leberl, Franz; Mayr, W; Domik, Gitta; Kobrick, M (International journal of remote sensing)

Representation independent query and update operations on propositional definite Horn formulas - Büning, Hans Kleine; Lettmann, Theodor (Computation Theory and Logic)

Image based SAR product simulation for analysis - Domik, Gitta; Leberl, Franz (ASPRS-ACSM)

A Hybrid Interpreter in a Software Development Environment - Engels, Gregor; Schürr, Andy (Proceedings of the 1st European Software Engineering Conference (ESEC '87), Strasbourg (France))
This paper describes the realization of an execution tool for Modula-2 modules which is part of an integrated tool set in a software development environment termed IPSEN (Incremental Programming Support Environment). In this environment, all software documents, e.g. Modula-2 modules, are manipulated by syntax-directed editors and are represented internally by attributed graphs. The execution of Modula-2 modules is done by two cooperating interpreters. The first one is a graph interpreter which traverses the internal graph from statement to statement. These statements are translated into a low-level, more efficiently executable object code and interpreted by a second interpreter. This concept of a hybrid interpreter allows the realization of an execution tool which offers a lot of runtime support features to the user.

On the Structure of Structure-Oriented Editors for Different Applications - Engels, Gregor; Nagl, Manfred; Schäfer, Wilhelm (Proceedings of the ACM SIGSOFT/SIGPLAN Software Engineering Symposium on Practical Software Development Environments, Palo Alto, USA)

Graph Grammar Engineering: A Software Specification Method - Engels, Gregor; Lewerentz, Claus; Schäfer, Wilhelm (Proceedings of the 3rd International Workshop on Graph-Grammars and Their Application to Computer Science, Warrenton, VA (USA))
Graphs as conceptual data models are accepted and used in a wide range of different problem areas. Giving some examples we outline common aspects for modeling complex structures by graphs. We present a formal frame-work based on graph grammars to specify graph classes and the corresponding graph manipulations. We show that such a specification can be written in a systematic, engineering-like manner. This is achieved by an extension of the known programmed, attributed graph grammars. Node-set operators are introduced to facilitate graph queries. Concepts like abstraction, decomposition, refinement, parameterization, and integration have been adopted from software engineering to yield a comprehensive specification method. This method has successfully been applied to specify the central data structures in a software development environment project

A Time-Space Tradeoff for Element Distinctness - Borodin, A.; Fich, F.; Meyer auf der Heide, Friedhelm; Upfal, E.; Wigderson, A. (SIAM Journal on Computing)

The Complexity of Parallel Sorting - Meyer auf der Heide, Friedhelm; Wigderson, Avi (SIAM Journal on Computing)

Digital Rectification Method for Radar Images Applied on Huge Arrays - Domik, Gitta (Proceedings of the First Int'l. Workshop on Image Rectification Tech. for Spaceborne Synthetic Aperture Radar)

Methods and application of surface shape reconstruction from multiple SAR images - Domik, Gitta (IGARSS'87-International Geoscience and Remote Sensing Symposium)

Methods and accuracy of operational digital image mapping with aircraft SAR - Leberl, Franz; Domik, Gitta; Mercer, Bryan J (1987 ASPRS ACSM Annual Convention)

Classes of first order formulas under various satisfiability definitions - Kleine Büning, H.; Lettmann, Theodor (8th International Conference on Automated Deduction)

Multiple incidence angle SIR-B experiment over Argentina: generation of secondary image products - Domik, Gitta; Leberl, Franz; Cimino, Jobea (IEEE Transactions on Geoscience and Remote Sensing)

Digital terrain mapping with STAR-1 SAR data - Mercer, JB; Lowry, RT; Leberl, Franz; Domik, Gitta (International Geoscience and Remote Sensing Symposium)